The relationship between diet, plasma glucose, and cancer prevalence across vertebrates - Stefania E. Kapsetaki; Anthony J. Basile; Zachary T. Compton; Shawn M. Rupp; Elizabeth G. Duke; Amy M. Boddy; Tara M. Harrison; Karen L. Sweazea; Carlo C. Maley (Nature Communications)
Abstract Birds have higher plasma glucose concentrations but lower cancer prevalence than other vertebrates. However, this inverse relationship between glucose and cancer may not hold within vertebrate groups. Given that diet affects blood sugar levels, and carnivores have higher cancer risk than herbivores, we also examined whether diet correlates with plasma glucose concentrations. We collected diet, mean plasma glucose concentration, and neoplasia data for up to 273 vertebrate species from existing databases. Across vertebrates, mean plasma glucose concentration negatively correlated with cancer prevalence, but that was mostly driven by differences in mean plasma glucose concentration and cancer prevalence between birds, mammals, and reptiles. Mean plasma glucose concentration was not correlated with diet across vertebrates nor with cancer prevalence within birds, mammals, or reptiles. Primary carnivores had higher neoplasia prevalence than herbivores when controlling for domestication. A hypothetical explanation for our results may be the evolutionary loss or downregulation of genes related to insulin-mediated glucose import in bird cells. This may have led to higher mean plasma glucose concentration, lower intracellular glucose concentrations in the form of glycogen, and production of fewer reactive oxygen species and inflammatory cytokines, potentially contributing to lower neoplasia prevalence in extant birds compared to mammals and reptiles.